A Comprehensive Study on the Performance of LIC of India Using the Caramel Model - Dr. B. Sandhya Rani; Dr. S. Ramesh (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
This research presents a comprehensive analysis of the performance of Life Insurance Corporation of India (LIC) using the CARAMEL model, which assesses key dimensions of an insurance company’s performance. The study reviews LIC’s financial data, market share, and customer feedback to evaluate its solvency, profitability, efficiency, and customer satisfaction. The literature review explores prior research on LIC’s performance evaluation and relevant performance models. The findings provide valuable insights into LIC’s strengths, weaknesses, opportunities, and challenges, and offer recommendations for enhancing its overall performance.